Observing Micro, Small, and Medium Enterprises (MSMEs) Readiness to Support Cashless Society - Shinta Maurizka Chairunnisa; Alfina Alfina; Annisa Yasmin (Bina Nusantara University, 2020)
Digital transformation in the era of the industrial revolution 4.0, has led to various new phenomena in today's people's lifestyle, including the payment transaction system. Realizing that Micro, Small and Medium Enterprises (MSMEs) had been one of the economy’s pillars in Indonesia, the government was trying to maximize the role of MSMEs to support the realization of a digital transaction ecosystem in Indonesia. With a phenomenological approach, the descriptive qualitative research aimed to provide in-depth observation and analysis on the readiness process of MSMEs in Tuban, East Java in adopting digital payment technology to support the realization of the trend of a cashless society. The results show that culture, social influence, and acceptance of technology are the dominant factors affecting the readiness process of MSMEs in Tuban in adopting digital payment technology.